Nanomaterial biocompatibility and antimicrobial effects on Escherichia coli - Sanober, Fahmi; Ahmad, Siti Khadijah; Wan Salim, Wan Wardatul Amani (Malaysia Society for Molecular Biology and Biotechnology, 2017)
We studied the effects of cultivating E. coli with nanomaterials involved in biosensor development. E. coli were cultured separately with each of these nanomaterials in Luria-Bertani broth medium. Bacterial growth curves were plotted by measuring optical density over a period of 12 hours, after which time bacterial cell dry weight was measured. After 12 hours of incubation, optical density was 0.588, 0.983, and 0.633 and cell dry weight was 4.6 × 10-3 g/ml, 4.9 × 10-3 g/ml, and 4.1 × 10-3 g/ml for bacteria cultivated in the presence of CNTs, AgNPs, and AuNPs respectively, suggesting that these nanomaterials have bactericidal or antimicrobial properties. On the other hand, graphene oxide (GO) does not have intrinsic bactericidal, cytotoxic, and/or antibacterial properties and greatly enhances bacterial growth. These findings advance our knowledge concerning the properties of nanomaterials and can guide the selection of appropriate nanomaterials for the fabrication of the transducer layer of a biosensor.